Friction stir welding and processing - Mishra, Rajiv S.; Mahoney, Murray W., 1945- (ASM International, 2007)
Progress in the understanding of corrosion and corrosion resistance properties of sintered stainless steels has lead to new applications that benefit from net shape processing and more efficient material utilization. The text, extensive graphics, and tabular summaries provide a comprehensive reference to obtain good corrosion resistance properties of sintered stainless steels with careful processing, starting with powder selection, avoidance of contamination, efficient delubrication, and controlled sintering and cooling. Misconceptions and conflicting literature are critically assessed.
Keywords: Friction welding.; elektronické knihy; electronic books